2015
DOI: 10.1097/ogx.0000000000000256
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Stress, Prematurity, and Asthma

Abstract: Asthma is the most common chronic disease of childhood, affecting millions of children in the U.S. and worldwide. Prematurity is a risk factor for asthma, and certain ethnic or racial minorities such as Puerto Ricans and non-Hispanic Blacks are disproportionately affected by both prematurity and asthma. In this review, we examine current evidence to support maternal psychosocial stress as a putative link between prematurity and asthma, while also focusing on disruption of the hypothalamic-pituitary-adrenal (HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 78 publications
2
20
0
1
Order By: Relevance
“…Against this background, our results suggest that it may be parietal cortex activity that drives the association between the approximate number system and formal math skills. On a functional level, this parallels the idea that structural features of parietal cortex correlate with formal math skills (Price et al, 2016) To conclude, while the absence of evidence may not be confounded with evidence for absence, considering the MVPA results, our study casts some doubt on the idea of a modeindependent numerosity representation in IPS. As the neural circuits for simultaneous and sequential numerosity comparison largely overlap in response trials, our results do not contradict with previous studies that used numerical tasks and reported common activation for both modes.…”
Section: Discussionsupporting
confidence: 77%
“…Against this background, our results suggest that it may be parietal cortex activity that drives the association between the approximate number system and formal math skills. On a functional level, this parallels the idea that structural features of parietal cortex correlate with formal math skills (Price et al, 2016) To conclude, while the absence of evidence may not be confounded with evidence for absence, considering the MVPA results, our study casts some doubt on the idea of a modeindependent numerosity representation in IPS. As the neural circuits for simultaneous and sequential numerosity comparison largely overlap in response trials, our results do not contradict with previous studies that used numerical tasks and reported common activation for both modes.…”
Section: Discussionsupporting
confidence: 77%
“…22 In addition, the literature reports that pre-mature newborn has increased salivary levels of pro-inflammatory cytokines, including interleukin-8, which acts as a potent neutrophil chemoattractant, causing inflammation of the airways. 22 Therefore, the increase in pro-inflammatory cytokines may be a risk marker for asthma. There are no studies demonstrating an association between HSPM and asthma, but MIH is associated with respiratory problems in general, including asthma.…”
Section: Discussionmentioning
confidence: 99%
“…; isolated from the watermelon and papaya were not chosen for further experiments due to it being pathogenic. Burkholderia is a genus of proteobacteria that refers to a group of gramnegative, obligate aerobic and rod-shaped bacteria [8]. Several members of this genus are prominent opportunistic pathogens where B. mallei and B. pseudomallei.…”
Section: A Identification Of Bc Producing Bacterial Strainsmentioning
confidence: 99%
“…Several members of this genus are prominent opportunistic pathogens where B. mallei and B. pseudomallei. B. cepacia, B. mallei, B. pseudomallei, B. cenocepacia, and B. pseudomallei can cause cystic fibrosis and are very challenging to treat [8]. Therefore, the subsequent study only focuses on isolate with ID number 003 in which isolate number 003 from mangosteen was identified as Enterobacter sp.…”
Section: A Identification Of Bc Producing Bacterial Strainsmentioning
confidence: 99%